2017
DOI: 10.1002/admi.201700912
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Mullite Formation in Ternary Oxide Coatings Deposited by ALD for High‐Temperature Applications

Abstract: coatings on geometrically complex substrates, [2][3][4] such as anodic aluminum oxide membranes, aerogels, photonic crystals, and nanorods, with a film thickness control on the Å-scale. Additionally, by combining two or more binary ALD processes in a super cycle ALD process, multicomponent materials can be achieved, such as nanolaminates, doped thin films, and ternary or quaternary oxides. [5] The ability of compositional control of thin films at an atomic level provides the possibility for development of tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The refractive indexes after ALD for the full titania and full alumina sample amounted to n = 2.187 ± 0.012 and 1.635 ± 0.002 (@632.8 nm), respectively, being in agreement with earlier reports [ 18 , 19 , 20 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 ]. All the other super-cycle samples fell within this interval ( Figure 2 ), indicating that the concept of tailor-made mixing of the oxides by variation of the sub-cycle ratio can be applied successfully.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The refractive indexes after ALD for the full titania and full alumina sample amounted to n = 2.187 ± 0.012 and 1.635 ± 0.002 (@632.8 nm), respectively, being in agreement with earlier reports [ 18 , 19 , 20 , 21 , 22 , 23 , 47 , 48 , 49 , 50 , 51 , 52 ]. All the other super-cycle samples fell within this interval ( Figure 2 ), indicating that the concept of tailor-made mixing of the oxides by variation of the sub-cycle ratio can be applied successfully.…”
Section: Resultssupporting
confidence: 91%
“…Atomic layer deposition is a process based on self-limiting surface-controlled chemical reactions between vaporized precursors and substrate, capable of producing a wide variety of materials comprising sulfides, selenides, tellurides, metals, nitrides, and oxides [ 13 ]. ALD has already been demonstrated for the production of inverse opal photonic crystals (iPhC) made from gallium phosphide [ 14 ], zinc sulfide [ 15 ], tungsten [ 8 ], zinc oxide [ 16 , 17 ], aluminum oxide [ 17 , 18 , 19 ], aluminosilicates [ 20 , 21 ], and titanium oxide [ 17 , 22 , 23 , 24 ]. In particular, the latter one is of interest for optical applications since titania features a relatively high refractive index, often higher than 2.3 at 632.8 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Mullite gels with two compositions, nearly stoichiometric low‐alumina 3Al 2 O 3 ·2SiO 2 (74 wt.% Al 2 O 3 , 26 wt.% SiO 2 ) and high‐alumina content 5Al 2 O 3 ·2SiO 2 (80 wt.% Al 2 O 3 , 20 wt.% SiO 2 ), were synthesized by sol‐gel, based in a procedure reported elsewhere . For the low‐alumina gel, a 50 mL sol was prepared by mixing 1 mol/L aluminum nitrate nonahydrate (ANN, 99.997% trace metals basis, Sigma‐Aldrich) prepared in a 50/50 vol.% water/ethanol with 50 vol.% tetraethyl orthosilicate (TEOS, ≥99.0%, Sigma‐Aldrich) aqueous solution.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, specific mullite studies are not so widespread when comparing to titania or zirconia. Synthesis of mullite by sol‐gel is well reported and can be tailored in a way that mullite forms already at temperatures as low as 1000°C . However, a very strict control of the sol‐gel and high‐purity precursors are necessary to produce a sol‐gel with low crystallization temperature for mullite (≤1000°C).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, ceramics are indispensable materials because they could be used in demanding environment due to their characteristic strong chemical stability and high temperature resistance. For example, Furlan reported that an Al 2 O 3 inverse opal coated with mullite could retain its 3D structure even at 1400°C. Although several kinds of ceramic TPCs had been reported in literatures, their THz properties were fixed after their creation.…”
Section: Introductionmentioning
confidence: 99%